TRAINING FOR FASILITATOR (TFF) DESA BERSIH DAN PENGELOLAAN SAMPAH 3R (BANK SAMPAH) DI DESA CIBODAS, KECAMATAN PASIRJAMBU, KABUPATEN BANDUNG - Ratnaningsih Ratnaningsih; Dwi Indrawati; Astri Rinanti; Asih Wijayanti (Jurnal AKAL : Abdimas dan Kearifan Lokal, 2020)
Cibodas Village, Pasirjambu District, Bandung Regency is a Partner Village for the Faculty of Landscape Architecture and Environmental Technology (FALTL) which has a vision of making Cibodas Village an Eco-Village. Waste management is one of the main activities to create an Eco-Village. One of the main problems in waste management is the use of the collect, transport and throw concept that has been entrenched in our society. The community, as a waste producer, is not yet disciplined in disposing of waste in its place and is not accustomed to implementing the 3R concept (Reduce, Reuse and Recycle). Activities ranging from preparation to implementation and writing of reports were carried out from June 2020 to August 15, 2020. The forms of activities were counselling and training. The activity took place on time and was attended by around 30 participants. The activity could run well and was followed by extension participants, namely the village youth who were assigned to be facilitators. Surveys conducted on June 2nd, 2020, discussed for training preparation, training material and participants. From outreach activities that focus on Counselling on Waste Management and Environmental Cleanliness as Efforts to Prevent Transmission of Infectious Diseases that have been carried out by the PKM Team of the Environmental Engineering Department, FALTL, Trisakti University can broaden facilitators' insights regarding waste management and prevention of transmission of infectious diseases and PKM activities are initial efforts to realize Eco-Village through community empowerment starting with independent waste management through 3Rs and waste banks.